The truth about the Devlins [large type] - Scottoline, Lisa (Thorndike Press, 2024)
"TJ Devlin is the charming disappointment in the prominent Devlin family, all of whom are lawyers at their highly successful firm-except him. After a stint in prison and rehab for alcoholism, TJ can't get hired anywhere except at the firm, in a make-work job with the title of investigator. But one night, TJ's world turns upside down after his older brother John confesses that he just murdered one of the clients, an accountant he'd confronted with proof of embezzlement. It seems impossible coming from John, the firstborn son and Most Valuable Devlin. TJ plunges into the investigation, seizing the chance to prove his worth and save his brother. But in no time, TJ and John find themselves entangled in a lethal web of deception and murder. TJ will fight to save his family, but what he learns might break them first."--